An Action Research at SDN Paji: Improving Students' Vocabulary Mastery through the Word Wall Strategy - Permata Sari , Dwi; Irmayani, Irmayani; Sofeny, Daniar (Perspektif Ilmu Pendidikan, 2025)
Learning English as a Foreign Language (EFL) requires vocabulary mastery, especially for elementary school students. This occurs due to limited teaching time, traditional teaching approaches, and low exposure to English. The descriptive qualitative method was used in this action research at SDN Paji, Lamongan. The purpose of this research is to determine how effective the Word Wall strategy is in improving the vocabulary of fifth-grade students. For six weeks, visuals, definitions, and example sentences were used to display thirty target words related to everyday themes. By reading aloud, using relevant words, and adding new vocabulary, students engaged with the Word Wall. Post-test results showed better recognition and usage of words in both speaking and writing, indicating a significant improvement in vocabulary mastery. Interviews confirmed that this method makes vocabulary learning more enjoyable and easier to remember, and observations showed an increase in students' confidence, participation, and ability to learn independently. According to self-determination theory, word boards also encourage intrinsic motivation. In addition, word boards support various different learning styles. By collaborating between teachers and students and incorporating additional preparation time into lesson plans, such issues can be addressed. Overall, the Word Wall strategy is student-centered and creates an interactive and cost-effective learning environment. This helps students learn vocabulary in an EFL environment with limited resources. Future research should investigate the long-term impact of digital adaptation at various grade levels.